MicroRNA-124 negatively regulates LPS-induced TNF-α production in mouse macrophages by decreasing protein stability - Sun Yang; Qin Zhen; Li Qi; Wan Jing-jing; Cheng Ming-he; Wang Peng-yuan; Su Ding-feng; Yu Jian-guang; Liu Xia (Acta Pharmacologica Sinica, 2017)
Aim: MicroRNAs play pivotal roles in regulation of both innate and adaptive immune responses. In the present study, we investigated the effects of microRNA-124 (miR-124) on production of the pro-inflammatory cytokine TNF-α in lipopolysaccharide (LPS)-treated mouse macrophages. Methods: Mouse macrophage cell line RAW264.7 was stimulated with LPS (100 ng/mL). The levels of miR-124 and TNF-α mRNA were evaluated using q-PCR. ELISA and Western blotting were used to detect TNF-α protein level in cell supernatants and cells, respectively. 3′-UTR luciferase reporter assays were used to analyze the targets of miR-124. For in vivo experiments, mice were injected with LPS (30 mg/kg, ip). Results: LPS stimulation significantly increased the mRNA level of miR-124 in RAW264.7 macrophages in vitro and mice in vivo. In RAW264.7 macrophages, knockdown of miR-124 with miR-124 inhibitor dose-dependently increased LPS-stimulated production of TNF-α protein and prolonged the half-life of TNF-α protein, but did not change TNF-α mRNA levels, whereas overexpression of miR-124 with miR-124 mimic produced the opposite effects. Furthermore, miR-124 was found to directly target two components of deubiquitinating enzymes: ubiquitin-specific proteases (USP) 2 and 14. Knockdown of USP2 or USP14 accelerated protein degradation of TNF-α, and abolished the effect of miR-124 on TNF-α protein stability. Conclusion: miR-124, targeting USP2 and USP14, negatively regulates LPS-induced TNF-α production in mouse macrophages, suggesting miR-124 as a new therapeutic target in inflammation-related diseases.